2012
DOI: 10.1063/1.4720093
|View full text |Cite
|
Sign up to set email alerts
|

Refrigeration effect in a single-level quantum dot with thermal bias

Abstract: We theoretically study the heat generation in a quantum dot (QD) connected simultaneously to two reservoirs and a local phonon bath. We find that driven solely by an external thermal bias, the resonant tunneling electrons can absorb heat from the phonon bath to the QD that are held at the same temperature. This QD refrigerator also works well under the thermoelectric effect. At room temperature and large thermal bias, the magnitude of the heat current density is on the order of nW/cm2 in typical Ge/Si QD, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…The magnitude of the heat generation is very small for negative thermal bias and becomes quite large for positive thermal bias. Moreover, the heat generation is negative in the negative thermal bias region, where the heat is flowing from the phonon bath to the QD and then the device behaves as a refrigerator as discussed in our previous work [34]. The origin of the the heat rectification effect can be explained as follows [40].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The magnitude of the heat generation is very small for negative thermal bias and becomes quite large for positive thermal bias. Moreover, the heat generation is negative in the negative thermal bias region, where the heat is flowing from the phonon bath to the QD and then the device behaves as a refrigerator as discussed in our previous work [34]. The origin of the the heat rectification effect can be explained as follows [40].…”
Section: Resultsmentioning
confidence: 95%
“…In the presence of ac bias voltage, finite time-dependent heat generation emerges without the accompany of electric current [32,33]. In our previous work, we have shown that electrons can absorb energy (phonons) from the phonon bath if the device is subjected to a temperature difference between the two ends of the device, behaving as a nano-refrigerator [34]. By adjusting the dot level, the heat generation can be very small for one direction of the temperature gradient, while it becomes quite large when the corresponding direction of the temperature gradient is reversed, which acts as a thermal diode [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the heat is generated due to the EPI, through which the energy associated with the electric current in central region is transferred to the phonon bath in the form of heat. They demonstrated that the law of the heat generation in macroscopic system, i.e., the Joule law, breaks down in zero-dimensional quantum-dot (QD) system and some unique behaviors of the heat current were predicted [13,14,[20][21][22][23][24][25][26][27]. For example, resonant phonon emitting occurs when the modified intradot Coulomb interaction is equal to the phonon energy, giving rise to a huge peak in heat generation despite a very weak electric current [14].…”
Section: Introductionmentioning
confidence: 96%
“…In the presence of external ac bias voltage, finite heat current can be driven out from the phonon bath without the accompany of electric current [20]. If the system is subjected to a thermal bias, we have found that the resonant tunneling electrons can drive heat out from the phonon bath to the central region that are held at the same temperature, and thus can be used as a nano-refrigerator [21]. A thermal rectifier or diode was also proposed by us with the help of the thermal bias [26].…”
Section: Introductionmentioning
confidence: 97%